The menagerie - Sutherland, Tui, 1978-; Sutherland, Kari H. (Harper, 2014)
Logan Wilde is let in on the secret Menagerie of Xanadu, Wyoming, when he wakes up to find a mythical griffin cub under his bed. This discovery leads him into contact with the strangest girl in seventh grade--Zoe Khan. The Khan family have guarded the Menagerie for centuries, but now someone is sabotaging them, and Zoe asks Logan for help to get the six griffin cubs back.